ACHIEVEMENT OF TARGET BLOOD PRESSURE LEVEL IN HYPERTENSIVE PATIENTS WITH AMLODIDINE: ORIGINAL DRUG VERSUS GENERIC - S. Yu. Martsevich; N. A. Dmitrieva; A. D. Deev; L. A. Sokolova; V. V. Jakusevich; J. V. Lukina; M. A. Maximova; A. V. Zaharova; A. A. Serazhim; V. P. Voronina (Столичная издательская компания, 2016)
Aim. To evaluate antihypertensive effects of new generic amlodipine (Stamlo M) in comparison with original amlodipine (Norvasc) in monotherapy and in combination with angiotensin converting enzyme (ACE) inhibitor and diuretic in patients with arterial hypertension (HT) of 1-2 degree.Material and methods. 60 patients with HT of 1-2 degree were included in the open randomized parallel comparative study. Patients were split into 2 groups. Study duration was 10 weeks. Efficacy control, dose correction, addition of ACE inhibitor and diuretic was performed each 2 weeks.Results. The significant antihypertensive effect of monotherapy was observed in both groups already by the 2-4 weeks of therapy. Significant differences between amlodipines in influence on blood pressure (BP) level and heart rate was not found. Monotherapy with generic amlodipine (10 mg OD) provided target BP level more than in half of patients. Achievement of target BP levels was found in 89% and 96% of patients treated with generic and original amlodipine, respectively, when they were combined with lisinopril (10 mg OD) and hydrochlorothiazide (12,5 mg OD).Conclusion. New generic amlodipine (Stamlo M) is an effective and safe antihypertensive drug comparable with original amlodipine in clinical efficacy.